(untitled) (Research, Society and Development, 2022)
Background: The goal of this cross-sectional study was to determine the mandibular third molar impaction in an adult Yemeni student using the Pell & Gregory and Winter classification. Methods: An orthopantomographic x-ray was used to assess 200 students (mean age 22.34 years), 102 males and 98 females. The data was subjected to statistical tests, which included age, gender, angulation, width, and impaction depth. Results: Of 345 mandibular third molars examined, mandibular third molars were congenitally missing in about 14% of the cases, approximately 7.5% in females and 6.5 % in males. According to Pell and Gregory’s classification, this study found a significant bilateral relation, with type A being the most prevalent in roughly half of the participants (61.4%). Type C, on the other hand, came in second with 22.9%, and this relationship was significant on both sides, particularly in women, who had greater mandibular third molar impaction than men. The vertical angulations of mandibular third molars showed the greatest vertical angulation (82.02%), followed by mesioangular (16.5%). Conclusion: The impaction pattern of mandibular third molars in Yemeni culture revealed a significant incidence of mesioangular, level B, and class II impaction, with more females than males.